User entrepreneurs for social innovation: The case of patients and caregivers as developers of tangible medical devices - Moritz Göldner; Cornelius Herstatt; Helena Canh\~ao; Pedro Oliveira (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2019)
Prior research has shown that some patients and caregivers such as relatives are innovating in relation to their unmet medical needs. However, there is little evidence whether and how these ideas are later implemented into market-ready solutions and subsequently commercialized. We analyze cases of patients and their caregivers becoming user entrepreneurs - persons who develop and market medical devices according to their own and/or their relatives' needs. We apply the framework of opportunity recognition and exploitation and conduct 14 case studies with medical device developers who have successfully brought their product to market. Our findings show that these innovation opportunities were mostly recognized during time-consuming and exhausting daily routines when no suitable medical device or other solutions were present. In 12 cases, the inventor founded a company to commercialize a product; in the remaining two cases, the idea was licensed after IP was secured. In all cases, the innovation had significant impacts on the quality of lives of the patients and, in case of caregivers, on both the patients and relatives. Since technical knowledge was not present in most cases, knowledgable friends and relatives were consulted and often integrated into the product development. The most prevalent motivation for further development and diffusion turned out to be the aspiration to validate the product idea and to deliver the benefits to others with the same ailment. This finding on innovation's social component complements current research on lead-users, as the solution of one's own problem was previously regarded as the key motivation. One major constraint to diffusing a medical device are regulations in the healthcare sector. Ten of 14 products in our sample were approved medical devices, with five classified as a higher-risk products and five as lower-risk products. We observe that patients and caregivers who recognize and exploit their ideas in the medical devices market did so despite particularly high market entry barriers in this sector. Few patients and caregivers were capable to bring even higher-risk medical devices to the market. This is unsurprising, because neither patients nor cargivers are experienced or trained to go through these time-consuming, demanding, and sometimes costly procedures. Healthcare companies should establish measures to support innovative patients and to systematically integrate them into their innovation processes.
Keywords: 330; user innovation; social innovation; user entrepreneurship; patient; caregiver; medical device; opportunity recognition; opportunity exploitation